Holistic well-being: a conceptual discussion integrating Islamic worldview, secular concepts and research findings - Mohd Nazori, Mohd Nazir; Abd Hamid, Hamidon; Ibrahim, Muhamad Ariff; Saad, Nurulwahida (IIUM Press, 2024)
Background: Holistic wellbeing is an elusive terminology. Defining such terminology differs according to perspective taken by the expert. Most discussion on the terminology originates from the secular paradigm with various perspectives being proposed. This paper aims to discuss the various secular perspectives and Islamic traditions on holistic wellbeing.